Effect of Implementation of Good Corporate Governance Financial Performance in Several State-Owned Companies in Indonesia - Nofiyanti, Rina (Accounting, 2010)
Good Corporate Governance is very important for the company, namely as a tool of management control in improving the performance of a healthy company. However, although many are aware of the importance of good corporate governance principles, many of those who reported low rate of company in Indonesia to implement these principles. Data used in this study are the companies that have implemented good corporate governance and companies in the top 10 ranking of the application of good corporate governance by IICG (The Indonesian Institute for Corporate Governance) in 2007 in the form of the rating score CGPI (Corporate Governance Perception Index ) and each company´s Annual Report reports that exist in 2007. The purpose of scientific writing is to know the effect of implementation of Good Corporate Governance Financial Performance Against Several Companies in Indonesia.From the research by using a simple linear regression, it can be concluded that the implementation of GCG (using GCG score) did not significantly affect the financial performance (in this study uses the ratio of corporate ROI), mean score GCG although the company has achieved a high score , the value is not significantly mempengharui ROI on enterprise level. Keyword: Good Corporate Governance, Financial Performance, ROI